Dall'amministrare all'amministrazione Le aziende nell'organizzazione statuale del Regno di Sardegna (1717-1853) - Stolfi, Giulio (Premio Ricerca «Città di Firenze», 2014)
This volume questions the hinges of modern statehood, through the reconstruction of the institutional story of subalpine companies. During the chronological period examined (1717-1853), the companies characterised the administrative structure of the Kingdom of Sardinia. Born as an original solution, part of a still complex and polycentric system of public powers, the companies - and with them the whole Savoy bureaucratic structure - were confronted with the progressive affirmation of the new categories of a 'closed', monadic, vertical state. The long path was marked by sharp accelerations (the revolution, the Napoleonic occupation, the affirmation of constitutionalism), but was also pervaded by strong affirmations of legal spontaneity.